2013
DOI: 10.1088/1741-2560/10/5/056004
|View full text |Cite
|
Sign up to set email alerts
|

Holographically patterned activation using photo-absorber induced neural–thermal stimulation

Abstract: Holographically patterned PAINTS could potentially provide a means for minimally intrusive control over neuronal dynamics with a high level of spatial and temporal selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 39 publications
4
81
0
Order By: Relevance
“…This study explored the effects of temperature changes on membrane capacitance and its associated currents in a joint attempt to clarify the experimental results of a key recent study [16] and to pave the way towards predictive modeling of INS [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and other thermal neurostimulation techniques [18][19][20], which could potentially facilitate the development of more advanced and multimodal methods for neural circuit control. Another key motivation to pursue this problem came from our noting the very similar temperature-related capacitance rates of change observed in very different model systems [ Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study explored the effects of temperature changes on membrane capacitance and its associated currents in a joint attempt to clarify the experimental results of a key recent study [16] and to pave the way towards predictive modeling of INS [2][3][4][5][6][7][8][9][10][11][12][13][14][15] and other thermal neurostimulation techniques [18][19][20], which could potentially facilitate the development of more advanced and multimodal methods for neural circuit control. Another key motivation to pursue this problem came from our noting the very similar temperature-related capacitance rates of change observed in very different model systems [ Fig.…”
Section: Discussionmentioning
confidence: 99%
“…5(a) of Ref. [18]], are inserted into model layer V cortical neurons. Reexamining in terms of the new biophysical model, α is almost entirely dependent on the temperature derivative of the membrane capacitance multiplied by the surface charge-related potential, allowing us to estimate the surface charge difference, Δσ ¼ σ i − σ o , as −0.107 C=m 2 plus maximal deviation ≈5% (note that α is identified as the neural membrane's thermoelectric capacitance; see Secs.…”
Section: Experimental Validation and Inferencementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Farah et al demonstrated electrical stimulation of rat cortical neurons with black micro-particles in vitro. They showed cell-level precision in stimulation using pulse durations on the order of hundreds of µs and energies in the range of µJ, potentially allowing for faster repetition rates 6 .…”
Section: Introductionmentioning
confidence: 99%